Preferences and attitudes to online help - Rowiński, Tomasz; Gągolewski, Marek (Studia Psychologica: Theoria et praxis, 2007)
The main purpose of this article is to begin a discussion about the possibility of providing online counseling and psychotherapy. In our study we tried to examine attitudes towards online and face-to-face (f2f) therapy in two groups: professionals and nonprofessionals. An online research was conducted in which 363 subjects participated. Overall, gender, being professional, having previous experience with counseling (f2f or online) and some Internetrelated variables have a significant impact on attitudes towards f2f or online therapy. We also propose a two-dimensional model which describes the preferences of online or f2f psychotherapy depending on the type of psychological crises in nonprofessional group. Practical considerations are reviewed.